Фізико-хімічна взаємодія в системах cBN–ТіВ₂–Al, cBN–ZrN–Al під час спікання під високим тиском і властивості одержаних композитів - Гарбуз, Т.О.; Кріштова, О.В.; Беженар, М.П.; Божко, С.А.; Білявина, Н.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The phase composition of the samples gained at a high pressure from an intermixture of two compositions (cBN–ТіВ₂–Al and cBN–ZrN–Al) is explored at change of temperature (1300–2300 K) and durations (5–300 s) sintering. Properties of samples (density, hardness, electroresistance) in connection with modes of a sintering are studied.